Germany The Reunification of a Nation - Bradley, Catherine; Co-Author (Gloucester Press Book New York, 1991)
Attempts to foresee what might be the political and economic significance of a reunited Germany. Reviews Germany's dark past in two world wars, its division into two hostile states, and past in two world wars, its division into two hostile states and the fears of Europeans and others of renewed German independence.
Includes index
Grade level : 4 - 6
Keywords: German reunification question -- Juvenile literature -- 1949; Politics and government -- Germany -- Juvenile literature -- 1945; Politics and government -- Europe -- Juvenile literature -- 1945